Between Fiqh and Adat: Negotiating Inheritance Law among the Bugis Community of Wajo - Husnul Fahimah Ilyas; Fakhriati Fakhriati; Muslimin A.R. Effendy; Musyfikah Ilyas (Universitas Islam Negeri Jakarta, 2026)
The Bugis community in Wajo has a distinct inheritance law that differs from those of other regions in Indonesia. In lieu of applying the law precisely as it is specified in Islamic fiqh, they adapt it to reflect the dominant local culture. The objective of this research is to elucidate the conflict between the Islamic fiqh-based inheritance law and the indigenous customs of the Bugis community residing in Wajo, South Sulawesi. By examining manuscript evaluations and oral traditions prevalent in the local community, this research uncovers the nature of contestation over inheritance distribution, as well as the factors and consequences that contribute to it. In the practice of inheritance division, the Bugis community in Wajo prioritizes the benefits of cohabitation to reduce disputes arising from asset division, according to this study's findings. Gender equality is of significant importance to them, and they regard mutual agreement as the standard by which they seek to reconcile legitimate interests and ensure an equitable distribution of inheritance. Abstrak Masyarakat Bugis di Wajo memiliki hukum waris yang berbeda dengan hukum waris di wilayah lain di Indonesia. Mereka tidak menggunakan hukum yang diterapkan dalam fikih secara an-sich, melainkan dimodifikasi dengan budaya lokal yang berlaku. Artikel ini mengungkap kontestasi yang terjadi antara hukum warisan yang dituangkan dalam fikih dengan budaya lokal yang dianut masyarakat Bugis di Wajo, Sulawesi Selatan. Metode penelitian ini bersumber dari manuskrip dan tradisi lisan yang digunakan dan berlaku dalam masyarakat setempat. Penelitian ini mengungkap wujud dari kontestasi yang terjadi dalam pembagian harta warisan, faktor, dan implikasi dari kontestasi tersebut. Hasil temuan penelitian ini menunjukkan bahwa dalam praktik pembagian warisan masyarakat Bugis di Wajo memprioritaskan kemashalahatan hidup bersama sehingga dapat meminimalisir konflik yang terjadi akibat pembagian harta warisan ini. Bagi mereka, kesetaraan gender menjadi perhatian khusus dan kesepakatan bersama menjadi tolak ukur untuk mencari solusi kemashlahatan dan keadilan dalam berbagi harta warisan.